2021
DOI: 10.21037/tcr-20-3035
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound alleviating myelosuppression of Sprague-Dawley rats after combined treating by paclitaxel and carboplatin

Abstract: Background: Our team has previously reported that low intensity pulsed ultrasound (LIPUS) can alleviate myelosuppression in rats induced by single chemotherapy drugs. But in clinics, chemotherapy is often performed with multiple drugs simultaneously. To be closer to the clinical status quo, this experiment was designed to show whether it was the same effect of LIPUS on myelosuppression caused by combination therapy of chemotherapy drugs.Methods: The rat model of myelosuppression was established by continuous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Notably, low-intensity ultrasound has been shown to suppress lipopolysaccharide-induced inflammatory responses by inhibiting TLR4 signal transduction. Therefore, low-intensity ultrasound may have biological effects in different tissues by affecting various signaling pathways (12)(13)(14)(15). A previous study reported that low-intensity ultrasound may reduce the phosphorylation of STAT3 in ovarian cancer stem cells through the interleukin 6 (IL-6)/STAT3 pathway (16).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, low-intensity ultrasound has been shown to suppress lipopolysaccharide-induced inflammatory responses by inhibiting TLR4 signal transduction. Therefore, low-intensity ultrasound may have biological effects in different tissues by affecting various signaling pathways (12)(13)(14)(15). A previous study reported that low-intensity ultrasound may reduce the phosphorylation of STAT3 in ovarian cancer stem cells through the interleukin 6 (IL-6)/STAT3 pathway (16).…”
Section: Introductionmentioning
confidence: 99%
“…Myelosuppression caused by chemotherapy, as reflected by decreased numbers of red blood cells, white blood cells (WBCs), and platelets according to the National Cancer Institute, can affect the quality of life and prognosis of patients. Once myelosuppression is induced, patients will be at risk of anemia, hemorrhage, or fatal infections. Unfortunately, complications may not only interrupt the course of chemotherapy or radiotherapy but also impede the therapeutic outcome. Currently, hematopoietic growth factors like granulocyte colony growth factors (G-CSFs), sargramostim (GM-CSF), and erythropoietin stimulating agents are used to regulate the hematopoietic function but they are expensive and are associated with adverse effects like bone pain and the risk of myocardial infarction, heart failure, stroke, and thrombosis …”
Section: Introductionmentioning
confidence: 99%